A dignity economy - Lindner, Evelin G. ([S.l.] : Dignity Press, 2011)
The economic crisis has many labels ranging from "subprime crisis" to "credit crunch," to "financial tsunami" or "economic Armageddon. Around the world, people are coming to a single diagnosis: "Something is deeply unhealthy in our world." This book advocates a deep paradigm shift, not just from one rigid paradigm to another rigid paradigm, but away from rigidity altogether. Away from massive institutions toward a global movement that is co-created by people and their enthusiastic energy. We need a dignity revolution, and not just in Tunisia or Egypt. Now we need a global dignity revolution, a world dignity movement, a movement that creates inclusion, both locally and globally. This book by the author of award winning books "Making Enemies - Humiliation and International Conflict", "Emotion and Conflict", as well as "Gender, Humiliation, and Global Security" provides an overview about the plurality of concepts and movements aimed at this.